2013
DOI: 10.1542/peds.2013-2024
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Outcomes of Young Adults Born Very Low Birth Weight

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Several studies have suggested that very low birth weight young adults have increased risks of physical and health problems, educational underachievement, and poorer social functioning than their peers, but there are limited population-based and longitudinal data.WHAT THIS STUDY ADDS: Former VLBW young adults in this national cohort scored as well as term controls on many measures of health and social functioning, including quality-of-life scores, with some differences largely con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 48 publications
(49 reference statements)
7
53
0
2
Order By: Relevance
“…7 The definitions of severe and moderate NDD were in keeping with those used in the EPICure cohort. 17 Estimates (95% confidence interval) of severe and moderate-tosevere NDD, respectively, for each GA were: (a) 22 weeks (n = 12): 31% (12,61) and 43% (21,69); (b) 23 weeks (n = 75): 17% (9,28) and 40% (27,54); (c) 24 weeks (n = 210): 21% (14,30) and 28% (18,41); and (d) 25 weeks (n = 441): 14% (10,20) and 24% (17,32). There was no statistically significant difference in the risk of severe NDD by week of GA but risk of moderate-to-severe NDD decreased by 6% for each increasing week of GA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The definitions of severe and moderate NDD were in keeping with those used in the EPICure cohort. 17 Estimates (95% confidence interval) of severe and moderate-tosevere NDD, respectively, for each GA were: (a) 22 weeks (n = 12): 31% (12,61) and 43% (21,69); (b) 23 weeks (n = 75): 17% (9,28) and 40% (27,54); (c) 24 weeks (n = 210): 21% (14,30) and 28% (18,41); and (d) 25 weeks (n = 441): 14% (10,20) and 24% (17,32). There was no statistically significant difference in the risk of severe NDD by week of GA but risk of moderate-to-severe NDD decreased by 6% for each increasing week of GA.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review yielded seven studies that assessed the self-reported QOL of adolescents/adults (17-23 years) who were extremely low birthweight (ELBW) or very low birthweight (VLBW) infants. 15,16,[25][26][27][28][29] Nearly all studies showed no significant difference in the self-rated QOL scores of former ELBW/VLBW infants compared with former full-term counterparts. They rated their QOL as good.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] This risk reduction may result from their cautious, shy, risk-avoidant personality style, 11,29 higher parental monitoring earlier in life, 16 or a later manifestation of their tendency to show lower levels of externalizing behavior in childhood and adolescence. 9,15,30 The finding that ELBW survivors were more likely to have a current non-substance use related psychiatric disorder is also in keeping with studies of VLBW survivors in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of very low birth weight (VLBW, ,1500 g) survivors in their 20s suggest that they may be at elevated risk for ADHD, mood disorders, anxiety, and social problems [8][9][10][11][12] but are less likely to have alcohol and substance use disorders. [13][14][15][16] Although few data exist on the adult mental health of ELBW survivors, these individuals may also be at elevated risk for depression, anxiety, and avoidant personality problems in their early to mid-20s. 17 Recent data suggest that people born at VLBW or ELBW may not be a homogeneous group in terms of risk.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[4][5][6] Poor school achievement has also been linked with a wide range of later adverse social, economic, and health outcomes well into adulthood. [7][8][9] The US National Education Goals Panel and, more recently, the American Academy of Pediatrics, have recommended a School Readiness Framework for assessing a child' s developmental progress and support needs before school entry to identify children at high risk who might benefit from proactive support as they transition to school. 10 This framework identifies 5 key "readiness to learn" domains spanning physical well-being and motor development, social and emotional development, approaches to learning, communication skills, and general knowledge and cognition.…”
mentioning
confidence: 99%